Reciprocal connectivity between mitral cells and external plexiform layer interneurons in the mouse olfactory bulb - Huang, Longwen; Garcia, Isabella; Jen, Hsin-I; Arenkiel, Benjamin R. (Frontiers in Neural Circuits, 2013)
Proper brain function relies on exquisite balance between excitation and inhibition, where inhibitory circuits play fundamental roles towards sculpting principle neuron output and information processing. In prominent models of olfactory bulb circuitry, inhibition of mitral cells by local interneurons sharpens odor tuning and provides contrast enhancement. Mitral cell inhibition occurs at both mitral cell apical dendrites and deep-layer dendrodendritic synapses between granule cells, the most abundant population of inhibitory interneurons in the olfactory bulb. However, it remains unclear whether other local interneurons make inhibitory connections onto mitral cells. Here, we report a novel circuitry with strong and reciprocal connectivity between a subpopulation of previously uncharacterized Corticotropin-Releasing Hormone (CRH) expressing interneurons located in the external plexiform layer (EPL), and mitral cells. Using cell type-specific genetic manipulations, imaging, optogenetic stimulation, and electrophysiological recordings, we reveal that CRH-expressing EPL interneurons strongly inhibit mitral cell firing, and that they are reciprocally excited by fast glutamatergic mitral cell input. These findings functionally identify a novel subpopulation of olfactory bulb interneurons that show reciprocal connectivity with mitral cells, uncovering a previously unknown, and potentially critical player in olfactory bulb circuitry that may influence lateral interactions and/or facilitate odor processing.